Pengembangan Instrumen Asesmen Kompetensi Minimum (AKM) Numerasi Model Pisa Dengan Konteks Musi Rawas Kelas V Sekolah Dasar - Trie Utari; Agus Susanta; Irwan Koto (Jurnal Kajian Pendidikan Dasar, 2024)
This study aims to analyze the logical feasibility, empirical and numeracy ability profile of students. Product development of the Minimum Competency Assessment (MCA)  numerical instrument PISA model with the context of Musi Rawas for 5th grade Elementary School. This research is a Research and Development (R&D) study and used the ADDIE model. The subjects of the research was the 5th grade students of SDN 1 Terawas, totaling 20 students to test eligibility empirically, and the 5th grade students of SDN Pasenan, totaling 18 students to analyze the profile of numeracy abilities. The numerical MCA consists of 17 questions in the form of multiple choice, complex multiple choice, and matching which are arranged using the MCA numeracy cognitive level and PISA 1-3 levels. Data data logically validity results has an index of more than 0.4 and is declared valid and logical. The results of empirical validity are 16 valid questions and 1 invalid question. The reliability value is 0.89 as "very high" category. Then the resulting product is 16 questions that are empirically feasible. For the analysis of the numeracy ability profile obtained from the average student numeracy MCA test scores based on the scores of each MCA level and PISA numeracy level it is known that the average student score at level 1 (comprehension) is 64, level 2 (implementation) the average student score namely 69, level 3 (reasoning) the average value of students is 57.